La competencia comunicativa y lingüística en la formación inicial de maestros: un estudio piloto - Marta Gràcia; Maria Josep Jarque; Marta Astals Murià; Kholoud Rouaz (Ignatianum University Press, 2019)
The assessment of communicative competence (speaking and listening) of students in initial teacher training is a field of study with few research despite its importance both for the learning process itself and for the subsequent professional performance. This article presents the results of a pilot study designed to identify the changes in the students' abilities from two groups in the initial teaching training when introducing a teaching innovation with the purpose of contributing to improve their oral communicative and linguistic competence. The evaluation instruments used are EVALOE and a rubric about the argumentative text. The results show the adequacy of these instruments as teaching innovation resources for both the improvement of the students' oral competence and its assessment.